Maqâshid al-Syarî`ah Paradigm for the Protection of Children Victims of Narcotics Abuse - Jamil, Syahril; Abdillah, Muhammad; Torik, Muhammad; Rostami, Soheila (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
Narcotics often cause children to become victims and it also affects the protection of children's rights. This study is intended to see how maqâshid al-syarî`ah views the protection of child victims of narcotics. The method used in this study was a descriptive qualitative approach to explore how paradigms, factors, and implications for the protection of child victims of narcotics. The data in this study was obtained through a search of a search engine google.com with the keyword